Algae as potential repository of anti cancerous natural compounds - Ankita Mridha; Santanu Paul (International Journal of Phytomedicine, 2017)
Algae constitute a promising source of novel compounds with potential as human therapeutic agents. In particular, algae have been considered as a potential source of new bio-active compound. Algae possess several biological activities, including anticancer activity. This review provides a comprehensive report on the several genera of algae belonging to Chlorophyceae, Pheophyceae and Rhodophyceae having anti-proliferative, apoptotic, anti angiogenic as well as cytotoxic efficacy and their mode of action in vitro as well as in vivo condition. Algae are extensively used as functional foods and medicinal herbs, and have a long history of use in Asian countries. Many algae have been used for the treatment of cancer, many crude or partially purified polysaccharides from various brown, green, and red algae have been tested for their antitumor activities. Relevant information was collected from scientific journals, books, and reports via library and electronic search using Medline, Pubmed, Science Direct, and Scopus. The different extracts with some other solvent shows a huge anti-proliferative action on different cancer as well as on different leukemia cell lines. Here we focus on several bioactive compounds that have been derived as well as characterized from different genera of algae and there mechanism of inhibiting cancer cell growth. Considering the ability of the golden treasure present in algae to act against different cancers, this review highlights the potential use of algae as anticancer agents.